Analisa Metode Mash-1 Untuk Mendeteksi Orisinalitas Citra Digital - Hotmian Gultom; Lince Tomoria Sianturi; Eferoni Ndruru (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The development of digital images is now very fast. Image data processing in digital images makes images easy to create or manipulate easily, without even leaving visual clues to the user. The ease of creating and changing an image can damage the credibility of the original image in various aspects. Small changes of pixels do not make image content detectable to the human eye. This is described in pixel like width and length in the image. the basis of this research to detect the authenticity of a digital image. This study will analyze the authenticity of the image and manipulation. This research is expected to produce and show good results in the form of evidence in detecting objects in the image so that it can help the public in determining the authenticity and manipulation of images.